Studi Docking Molekuler Catechin Gallate, Epicatechin Gallate, Gallocatechin Gallate, dan Epigallocatechin Gallate - Isnawati, Ani; Adelina, Rosa (Jurnal Kefarmasian Indonesia, 2015)
Indonesia has the second biggest natural in the world. This natural resources could be used as raw material for drug if well managed. As we know, 96% of raw material in Indonesia are imported which caused the price of drugs are expensive. In order to overcome the problem, it is essential to conduct research about Indonesian plants which are potential as dyslipidemia drug. The molecular docking study is one of insilico studies that is used to screen compounds based on their working mechanism to protein. In this study, catechin gallate, epicatechin gallate, gallocatechin gallate and epigallocatechin gallate were docked using Moleculer Operating Environtment (MOE). Software in order to determine their affinity and interaction with HMG-CoA reductase enzyme which has a role in cholesterol/fat metabolism. This research used simvastatin and atorvastatin as the standard drug for dyslipidemia. The result of molecular docking showed that Gibbs values of simvastatin, atorvastatin, catechin gallate, epicatechin gallate, gallocatechin gallate and epigallocatechin gallate were -6,4974; -8,543; -9,5736; -10,6395; -10,4765; and -10,598. The results stated that four cathechin derivates have an inhibiting energy better than simvastatin and atorvastatin. These are potential as dyslipidemia drugs candidate.